New species of Hybos Meigen from Northwest China (Diptera: Empidoidea, Hybotinae) - Li, Zhu; Wang, Ning; Yang, Ding (Zootaxa, 2014)
The species of the genus Hybos Meigen from Northwest China are reviewed. The following five species are described as new to science: Hybos elongatus sp. nov., H. flavitibialis sp. nov., H. projectus sp. nov., H. qinlingensis sp. nov., and H. xii sp. nov. A key to the 17 species of the genus Hybos from Northwest China is provided.